2009
DOI: 10.1094/pdis-93-7-0699
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Field-Source Mixture of Citrus Viroids on the Performance of ‘Nules’ Clementine and ‘Navelina’ Sweet Orange Trees Grafted on Carrizo Citrange

Abstract: A field-source mixture of citrus viroids was characterized and shown to contain Citrus exocortis viroid (CEVd), Hop stunt viroid (HSVd), Citrus bent leaf viroid (CBLVd), and Citrus dwarfing viroid (CDVd). Sequencing results showed that: (i) CEVd contained the PL and PR characteristic of class A variants; (ii) HSVd was a noncachexia variant; (iii) CBLVd was related to CVd-Ia variants; (iv) CDVd was a mixture of two types (CVd-IIIa and CVd-IIIb) of variants. The presence of the same type of variants in inoculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In the case of viroid–host interactions, only limited information is available, but long‐term studies performed with citrus trees revealed that viroid‐infected trees presented a smaller root–shoot system. These plants presented only a small number of parenchyma cells containing stored carbohydrates relative to noninfected control plants (Bani Hashemian et al ., 2009). This effect is caused by a reduced source–sink transport, resulting in an unbalanced root–canopy system and, consequently, in the dwarfing associated with viroid infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of viroid–host interactions, only limited information is available, but long‐term studies performed with citrus trees revealed that viroid‐infected trees presented a smaller root–shoot system. These plants presented only a small number of parenchyma cells containing stored carbohydrates relative to noninfected control plants (Bani Hashemian et al ., 2009). This effect is caused by a reduced source–sink transport, resulting in an unbalanced root–canopy system and, consequently, in the dwarfing associated with viroid infection.…”
Section: Discussionmentioning
confidence: 99%
“…The relation of auxin to viroid infection was reported by Duran‐Vila and Semancik (1981), who showed the inability of tomato tissue infected with CEVd to respond to exogenous auxins. This inability might be involved in the development of the pathogenic syndrome caused by CEVd, not only in tomato, but also in Carrizo citrange (Bani Hashemian et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Symptom evaluation was complex because trees grafted on these rootstocks were more tolerant of viroid infection, and the environmental conditions (mainly temperature) did not enhance symptom expression (Figure 4). By pulling out the trees, we were able to see/evaluate mild symptoms as well as the effect of viroid infection on the root size and therefore canopy size [41,42]. Such results were also confirmed by evaluating the performance of viroid infected trees in commercial plantations [43].…”
Section: Field Assays Supporting Viroid Characterizationmentioning
confidence: 91%
“…For non-EU CTV isolates, in the EPPO A2 List, which are responsible for field stem pitting (SP) on sweet orange regardless of rootstock, and resistance-breaking (RB) of trifoliate orange and its hybrids [10], EU member states are required to plan annual surveys using a statistically sound and risk-based approach, in line with current international standards [4]. CBCVd, the smallest of the citrus viroids, a chimeric recombinant viroid between citrus exocortis viroid (CEVd) and hop stunt viroid (HSVd) [11], induces severe symptoms on trifoliate orange and Carrizo citrange [12,13].…”
Section: Introductionmentioning
confidence: 99%